Development of functional balance training tasks for stroke rehabilitation: a Delphi study with Pakistani experts - Ayesha Afridi; Samman, Rohma; Arshad Nawaz Malik (Journal of the Pakistan Medical Association, 2026)
Objective: To develop functional balance training tasks for stroke rehabilitation to enhance recovery outcomes for stroke patients. Method: A cross-sectional study employing a two-phase structured Delphi technique was conducted in Rawalpindi and Islamabad, Pakistan, from August to December 2023, following approval from the ethics review committee of Riphah College of Rehabilitation and Allied Health Sciences, Islamabad. In the first phase, a list of functional balance tasks was generated through literature review and semi-structured interviews with experts. In the second phase, iterative three-round Delphi survey was conducted with a larger panel. Descriptive statistics were used at the end of each round to finalise the list of functional tasks based on pre-set consensus criteria. Data was analysed using SPSS 25. Results: Of the 10 experts in Phase 1, there were 8(80%) females and 9(90%) had postgraduate qualification in Neuromuscular Physical Therapy, while the mean professional experience was 6.1±5.17 years. The corresponding values for the 30 experts in Phase 2 were 34(80%), 29(96%) and 5.48±5.08. In Phase 1, 100 functional balance tasks were generated. In Round 1 of Phase 2, 76 tasks met the consensus criteria of >60% agreement. In Round 2 of the phase, 52 tasks reached consensus criteria of >75% agreement, while in Round 3 of the phase, 50 tasks achieved consensus of >80% agreement. Conclusion: An evidence-based list of functional balance tasks for stroke rehabilitation was deemed suitable by local experts for stroke patients in Pakistan. Key Words: Rehabilitation, Delphi technique, Stroke, Postural balance.